2008
DOI: 10.1007/s11205-008-9306-8
|View full text |Cite
|
Sign up to set email alerts
|

Folk Theories of Happiness: A Cross-Cultural Comparison of Conceptions of Happiness in Germany and South Africa

Abstract: Happiness, Folk theory, Germany, South africa,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 41 publications
4
75
0
5
Order By: Relevance
“…This is a serious limitation and more exploratory studies are needed to create a more culture-fair methodology. Research indicates that individual conceptions of happiness are to some extent universal (Pflug 2009) but that culture and society are both important in determining how people perceive happiness (Delle Fave et al 2013b;Joshanloo 2012), suggesting that concepts of happiness are culture-specific. Analysis of happiness categories ought to take into account the particular cultural domain and data gathering should, as far as possible, be free from assumptions about the nature of happiness so that participants can freely describe their understanding of happiness.…”
Section: Lay Conceptions Of Happinessmentioning
confidence: 99%
“…This is a serious limitation and more exploratory studies are needed to create a more culture-fair methodology. Research indicates that individual conceptions of happiness are to some extent universal (Pflug 2009) but that culture and society are both important in determining how people perceive happiness (Delle Fave et al 2013b;Joshanloo 2012), suggesting that concepts of happiness are culture-specific. Analysis of happiness categories ought to take into account the particular cultural domain and data gathering should, as far as possible, be free from assumptions about the nature of happiness so that participants can freely describe their understanding of happiness.…”
Section: Lay Conceptions Of Happinessmentioning
confidence: 99%
“…We did not propose any specific hypothesis about the content category 'opposite of happiness'. We explored whether this category was present in children and adolescents' definitions to a similar degree as in adults' definitions, in which 19% of participants defined happiness in terms of this content category (Pflug, 2009). …”
Section: Study 2: Children's and Adolescents' Conception Of Happinessmentioning
confidence: 99%
“…Russia > USA (Beekun et al, 2005;Ahmed et al, 2003) South Africa > Germany (Pflug, 2008) Croatia > USA (Tavakoli et al, 2003) Taiwan > USA (Lu, 2001;Cherry et al, 2003) Spain > Mexico (Husted et al, 1996) Egypt > USA (Marta et al, 2003) Ukraine > USA (Kennedy & Lawton, 1996) Taiwan > Australia > USA (Allmon et al, 1997) X China > EU (Vittel and Patwardhan, 2008) El Salvador > USA = Canada (Chiasson et al, 1996) Malaysia > USA (Karande et al, 2000) India > USA (Kracher et al, 2002) India = China = Malaysia (Zabid & Ho, 2003;Zabid & Ibrahim, 2008) Philippines > USA (Vasquez et al, 2001) Chile > Australia (Robertson et al, 2002) Mexico > Spain (Husted et al, 1996) Malaysia > New Zealand (Goodwin & Goodwin, 1999) China > Australia (Tsui & Windsor, 2001) II USA = Canada > El Salvador (Chiasson et al, 1996) USA > Russia (Beekun et al, 2005;Ahmed et al, 2003) USA > Philippines (Vasquez et al, 2001) Norway > USA (Falkenberg, 1998) Germany > South Africa (Pflug, 2008) Australia > USA X USA > Egypt (Marta et al, 2003) USA > Taiwan (Lu, 2001;Cherry et al, 2003) USA > Ukraina (Kennedy & Lawton, 1996) USA > Norway (Falkenberg, 1998) USA > Brazil (Volkema and Fleury, 2002) USA ...…”
Section: 2happiness Predicted By the Modelmentioning
confidence: 99%
“…A "by product" of this first purpose will be a ranking of ethical approaches in terms of individual happiness as dependent of individual characteristics. Next, there is a huge psychological, social and economic literature aiming at motivating (for recent examples, Pflug, 2008;Lu, 2001) or at assessing (for recent examples, Welsch, 2003;Peirò, 2006;Inglehart et al, 2008;Heylighen and Bernheim, 2000;Haller and Hadler, 2006;Veenhoven, 2005;Hayo, 2007;Lelkes, 2006) the observed differences in happiness contents in different countries or cultures, on the one hand; on the other hand, at justifying (for recent examples, Robertson and Crittenden, 2003;Gossling, 2003;Jensen, 2008) or at measuring (for recent examples, Brammer et al, 2006;Franke andNadler, 2008, Forsyth et al, 2008;Guiso et al, 2003;Cherry et al, 2003;Beekun et al, 2005;Ahmed et al 2003;Singhapakdi et al, 2001;Karande et al, 2000;Tavakoli et al, 2003;Vasquez et al 2001;Volkema & Fleury, 2002;Lu & Gilmour, 2004;Robertson et al 2002;Zabid and Ho, 2003;Zabid and Ibrahim, 2008;Kracher et al, 2002;Vittel and Patwardhan, 2008;Marta et al, 2001;Blodgood et al, 2008) the observed differences in ethical approaches prevailing in different countries or cultures. The second purpose of this paper is to apply the analytical model to explain the observed differences in happiness in different countries or cultures in terms of the observed different ethical approaches prevailing in different countries or cultures, under very plausible assumptions.…”
Section: Introductionmentioning
confidence: 99%